Nitrate and Prussic Acid Toxicity in Forage - Fjell, Dale; Blasi, Dale; Towne, Gene (My University, 1991)
This publication describes how to avoid prussic acid poisoning and describes why nitrates are toxic.
MF1018_1991_11
Keywords: MF1018; Crops; Livestock; Health and Safety; MF